2021
DOI: 10.1186/s12888-021-03119-z
|View full text |Cite
|
Sign up to set email alerts
|

Global and reflective rumination are related to suicide attempts among patients experiencing major depressive episodes

Abstract: Background Recent attention has focused on the role of rumination in suicidality, with evidence indicating that rumination may be positively related to suicidal ideation. There remains disagreement on the nature of the relationship between rumination and suicide attempts, especially in major affective disorders. This study was designed to identify whether rumination is a risk factor for attempted suicide. Methods A total of 309 patients with major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 48 publications
1
8
0
1
Order By: Relevance
“…In this study, there was a positive correlation between rumination and suicidal ideation, indicating that a higher rumination score on admission may signify more serious suicidal ideation. A previous study found that correlations between depression symptoms and rumination and between suicidal thoughts that persisted over a long period and rumination were similar [ 14 ]. Depressive symptoms and rumination can both predict suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there was a positive correlation between rumination and suicidal ideation, indicating that a higher rumination score on admission may signify more serious suicidal ideation. A previous study found that correlations between depression symptoms and rumination and between suicidal thoughts that persisted over a long period and rumination were similar [ 14 ]. Depressive symptoms and rumination can both predict suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Treynor et al divided rumination into (1) reflection (facing and solving problems and difficulties), and (2) brooding (discouraged and frustrated). The brooding style and reflection style of rumination had an impact on suicide attempts [ 14 ]. Rumination can predict suicide [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies provided information about how trait-levels of ACCs relate to STBs and how these relations change across long timescales often spanning months or years, offering insight into which individuals are at overall elevated risk for STBs (Franklin et al 2017;Turecki and Brent 2016). In general, higher positive affect (e.g., Han et al 2022) associates with lower STB risk, while higher negative affect (e.g., Yamokoski, Scheel, and Rogers 2011), rumination (e.g., Tang et al 2021), distress intolerance (e.g., Slabbert et al 2022) and emotion dysregulation (e.g., Wallace et al 2023) associate with elevated STB risk in cross-sectional and panel studies.…”
Section: Affective-cognitive Constructs (Accs) As Risk Factors For Stbsmentioning
confidence: 99%
“…Клинические исследования говорят о том, что руминации «мрачно-задумчивого» типа в бóльшей степени связаны с риском хронификации депрессии и суицидальным риском [29; 33], в то время как рефлексивные (более активные) руминации способствуют уменьшению депрессии с течением времени [38]. При этом в одном из последних исследований показан противоположный результат: именно рефлексивные руминации при контроле социодемографических и клинических факторов выступили предиктором суицидального риска [39].…”
Section: поиск и проверка валидности инструментарияunclassified